2016
DOI: 10.1007/s10040-016-1412-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping groundwater storage variations with GRACE: a case study in Alberta, Canada

Abstract: The applicability of the Gravity Recovery and Climate Experiment (GRACE) to adequately represent broad-scale patterns of groundwater storage (GWS) variations and observed trends in groundwater-monitoring well levels (GWWL) is examined in the Canadian province of Alberta. GWS variations are derived over Alberta for the period 2002-2014 using the Release 05 (RL05) monthly GRACE gravity models and the Global Land Data Assimilation System (GLDAS) land-surface models. Twelve mean monthly GWS variation maps are gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In recent years, there have been many studies of the retrieval of groundwater changes in different regions using the GRACE satellite gravity data and hydrological models. These studies have been performed in areas including the Mississippi River basin [8], Northern India [9,10], the Mid-Atlantic Region [11], East Africa [12], the Indus Basin in Pakistan [13], the Tibetan Plateau [14], the Three Gorges Reservoir of China [15], the North China Plain [2,16], Alberta in Canada [17], the whole area of Jordan [18], and other regions [19][20][21]. These studies found good correspondence between GWS changes from GRACE and situ GWS changes from monitoring wells, which indicate that GRACE shows great potential for monitoring large-scale GWS changes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been many studies of the retrieval of groundwater changes in different regions using the GRACE satellite gravity data and hydrological models. These studies have been performed in areas including the Mississippi River basin [8], Northern India [9,10], the Mid-Atlantic Region [11], East Africa [12], the Indus Basin in Pakistan [13], the Tibetan Plateau [14], the Three Gorges Reservoir of China [15], the North China Plain [2,16], Alberta in Canada [17], the whole area of Jordan [18], and other regions [19][20][21]. These studies found good correspondence between GWS changes from GRACE and situ GWS changes from monitoring wells, which indicate that GRACE shows great potential for monitoring large-scale GWS changes.…”
Section: Introductionmentioning
confidence: 99%
“…Much before the current digital revolution, there has been a long record of using remote sensing technologies to address this challenge, going back at least to the launch of Landsat-1 (then called Earth Resources Technology Satellite) in 1972, followed more recently by the era of Earth Observing Systems (EOS) with the launch of the Terra satellite in 1999 (Melesse et al, 2007). Remote sensing has been extensively used to monitor, among other things, the status of forest resources (Lefsky et al, 2002), larger mammals and birds in open habitats (Leyequien et al, 2007), capture fisheries (Santos, 2000), and ground water resources (Huang et al, 2016). Another example, at a more local level, is the detection via remote sensing of increased turbidity in the Northern Poyang Lake, the People's Republic of China (hereafter "China"), which resulted in a ban on sand mining (Wu et al, 2007;de Leeuw, 2010).…”
Section: Improving the Monitoring And Supervision Of Imperfectly Obsementioning
confidence: 99%
“…Estimates of groundwater storage using the remote sensing have been performed around the globe (Swenson et al, 2006;Rodell et al, 2007Rodell et al, , 2009Strassberg et al, 2007;Tiwari et al, 2009;Scanlon et al, 2012;Shamsudduha et al, 2012;Voss et al, 2013;Bhanja et al, 2014Bhanja et al, , 2016Bhanja et al, , 2017bBhanja et al, , 2018Richey et al, 2015;Panda and Wahr, 2016;Chen et al, 2016;. Huang et al (2016) used remote-sensing data for computing the groundwater storage anomalies (GWSAs) in order to estimate groundwater storage in Alberta. They used groundwater levels (GWLs) at 36 wells, mostly confined to the southern Alberta region, and were correlated with both the GRACE terrestrial water storage (TWS) and groundwater storage variations.…”
Section: Introductionmentioning
confidence: 99%